2012
DOI: 10.1111/iju.12015
|View full text |Cite
|
Sign up to set email alerts
|

Intrarenal reflux in primary vesicoureteral reflux

Abstract: Abbreviations & AcronymsObjectives: To elucidate the significance of intrarenal reflux. Methods: We retrospectively analyzed 276 patients (age <5 years) with grade III to V vesicoureteral reflux. They were divided into two groups: 55 patients with intrarenal reflux and 221 patients without intrarenal reflux (control group). All patients received low-dose antibiotic prophylaxis. Results: The most common initial presentation in both groups was febrile urinary tract infection. On dimercaptosuccinic acid scan, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 13 publications
2
13
0
2
Order By: Relevance
“…Moreover, IRR tends to form parenchymal scars in 26-65% of cases over time (5,10,11). Boubnova et al found that the possibility for the breakthrough of urinary tract infections during long-term antibiotic prophylaxis is the same in the group of patients with high grade of VUR and IRR as in those with high-grade VUR but without IRR, whereas some other authors confirmed that patients with IRR had significantly more breakthrough infections than those without IRR (12,13). It seems that IRR is equally distributed in both genders and that it is present only in patients with higher grades of VURs (III, IV, and V grade), while it has not been observed in patients with lower grades of VURs (grades I and II) on VCUG (9).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, IRR tends to form parenchymal scars in 26-65% of cases over time (5,10,11). Boubnova et al found that the possibility for the breakthrough of urinary tract infections during long-term antibiotic prophylaxis is the same in the group of patients with high grade of VUR and IRR as in those with high-grade VUR but without IRR, whereas some other authors confirmed that patients with IRR had significantly more breakthrough infections than those without IRR (12,13). It seems that IRR is equally distributed in both genders and that it is present only in patients with higher grades of VURs (III, IV, and V grade), while it has not been observed in patients with lower grades of VURs (grades I and II) on VCUG (9).…”
Section: Introductionmentioning
confidence: 99%
“…VUR is the most common congenital urinary tract abnormality in children that usually presents with urinary tract infection (UTI) [2]. It is conventionally diagnosed and followed by voiding cystourethrogram (VCUG) that classifies the disease into five grades (I to V) [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Children with VUR are in the danger of frequent pyelonephritis that may lead to the development of kidney scare and progressive kidney dysfunction [5][6][7][8]. When associated with intrarenal reflux, it decreases the renal function, and increases UTI incidence [4,5]. VUR may also resolve spontaneously [3], but complications may occur even after resolution of VUR [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3), den Refluxgrad mit oder ohne intrarenalem Reflux, einesoweit beurteilbarkonkomittante Blasenfunktionsstörung und der Präputialstatus des männlichen Säuglings [30]. Der intrarenale Reflux in Zusammenhang mit dilatierendem VUR (III-IV) sowie nachgewiesene Parenchymdefekte im DMSA-Scan stellen unabhängige Risikofaktoren für Durchbruchsinfekte wie weitere Parenchymschädigungen dar [31] (▶ Abb. 4).…”
Section: Introductionunclassified